2016
DOI: 10.3389/fnagi.2016.00175
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine Dithiocarbamate Prevents Neuroinflammation and Cognitive Dysfunction after Endotoxemia in Rats

Abstract: Systemic inflammation, for example as a result of infection, often contributes to long-term complications. Neuroinflammation and cognitive decline are key hallmarks of several neurological conditions, including advance age. The contribution of systemic inflammation to the central nervous system (CNS) remains not fully understood. Using a model of peripheral endotoxemia with lipopolysaccharide (LPS) we investigated the role of nuclear factor-κB (NF-κB) activity in mediating long-term neuroinflammation and cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 55 publications
(58 reference statements)
3
30
0
Order By: Relevance
“…Previous studies have demonstrated that intraperitoneal administration of LPS leads to spatial learning and memory deficits [ 7 , 31 ]. Therefore, the protective effects of BAI on LPS-induced cognitive deficits were examined in this well-established mouse model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that intraperitoneal administration of LPS leads to spatial learning and memory deficits [ 7 , 31 ]. Therefore, the protective effects of BAI on LPS-induced cognitive deficits were examined in this well-established mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…), (iii) LPS+BAI (2 mg/kg LPS i.p.+103 mg/kg BAI, intragastric gavage i.g., daily), (iv) BAI alone (103 mg/kg), (v) BAI+LPS+EX-527 (a selective SIRT1 inhibitor, 5 mg/kg/day, every 2 days for a total of 7 days before LPS and 5 mg/kg/day after LPS), and (vi) LPS+EX-527. We chose this LPS dose based on previous studies in which LPS at 2 mg/kg reliably induced sickness behavior and learning deficits in C57BL/6 J mice [ 31 , 32 ]. The chemical structure of BAI is shown in Figure 1(a) .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, PDTC has effective anti-inflammatory and anti-tumor properties [14]. Previously, several studies have shown that PDTC can affect inflammation, such as by inhibiting ultraviolet B-induced skin inflammation and by preventing neuroinflammation and cognitive dysfunction after endotoxemia [15,16]. However, few studies have clarified the relationships among PDTC, TLR4, NF-κB and peri-implantitis.…”
Section: Introductionmentioning
confidence: 99%
“…The training process was performed as described in our previous study with some modifications. [ 25 ] Briefly, the MWM test was divided into two parts: spatial acquisition trials (days 1–5) and probe trial (day 7). The rats were rested on day 6.…”
Section: Methodsmentioning
confidence: 99%
“…[ 8 , 21 ] Because neuroinflammation has been proved to be a major cause for AD [ 22 ] and PD [ 23 ] in aged patients, aged rats are an ideal choice for mechanism studies. [ 24 , 25 ] However, doses of inhalational anesthetics in aged rats differ from those used in adults. [ 26 ] Meanwhile, the levels of important neural receptors in CNS, including γ-amino butyric acid A (GABA A ) receptors [ 27 ] and N-methyl-D-aspartate receptors [ 28 ] also modulate with aging, indicating that the effect of anesthesia on aged brain requires further study.…”
Section: Introductionmentioning
confidence: 99%